PENGARUH KUALITAS PRODUK, INOVASI PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK HI JACK SANDALS BANDUNG - admin admin; Diah Ernawati (Universitas Lambung Mangkurat, 2019)
This study aims to determine and analyze the influence of product quality, product innovation and promotion to product purchase decision of